Gender conflict resolution in Nigerian and African American standup performances - Idowu James Adekunle (International Journal of Visual and Performing Arts, 2023)
Stand-up comedy, a prominent facet of live theatrical entertainment, occupies a unique position in the entertainment industry, embodying a key element of popular culture. This comedic form reflects the sociological dynamics of both historical and contemporary societies, influencing and engaging both local and international audiences. Beyond providing psycho-physical therapy for performers, stand-up comedy plays a pivotal role in shaping societal perceptions. This article focuses on a gender-focused analysis of stand-up comedy, exploring its implications for domestic growth, marriage unity, and love. Utilizing three digital recordings featuring stand-up comedians, namely Bright Okpocha (Basket Mouth), Ayo Makun (AY), and Eddie Murphy, the study examines their unique approaches to addressing gender-based violence and resolving conflicts. The selection criteria were based on the comedians' distinct counseling methods and perspectives on gender-related issues. Drawing on Richard Schechner's performance theory, the analysis employs both performance and content analyses to elucidate the spectrum of gender conflicts and resolutions presented by the comedians. The findings underscore the importance of mutual understanding and communication in resolving gender conflicts. The article also delves into the influence of parental roles in household management and the pursuit of material wealth. Emphasizing the significant role of counseling modes, the study concludes that stand-up comedy, with its oratory counseling mode and therapeutic elements, serves as an effective means of addressing gender conflicts, contributing to mutual understanding and successful resolutions within society.